Wish you were here - Picoult, Jodi. (London : Hodder & Stoughton, 2021)
"Diana O'Toole is perfectly on track. She will be married by thirty, done having kids by thirty-five, and move out to the New York City suburbs, all while climbing the professional ladder in the cutthroat art auction world. She's a junior appraiser at Sotheby's now, but her boss has hinted at a promotion if she can close a deal with a high-profile client. She's not engaged just yet, but she knows her boyfriend Finn, a surgical resident, is about to propose - days before her thirtieth birthday. Right on time. But now she is stranded, alone on what was planned to be a romantic idyll with Finn. Unfortunately, Finn is trapped worlds away, and Diana is on one of the world's most beautiful islands with no food, no luggage, and no place to stay, forced to test her personal limits and survive. Struggling to find her feet, Diana gradually connects with a local family when a teenager with a secret opens up to her. As Diana helps her fight her demons she learns more about herself, and about the island of Galapagos, where Darwin developed his theory of evolution. The dramatic and sometimes dangerous terrain reflects Diana's own experiences, her new relationships and growing awareness that she too is evolving into someone quite different. A near-death experience brings Diana abruptly back to familiar city surroundings, where she tries to pick up the threads of her old life. Has she changed or have the people around her? Diana is no longer prepared to be just a follower, at work or in her relationships. She breaks down years of a stunted relationship with her mother, takes the initiative in her career, and looks at Finn through new eyes."--Publisher
Keywords: Modern & contemporary fiction; Fiction & related items; FICTION |x -- Family Life -- General